Twin arginine translocation system in secretory expression of recombinant human growth hormone - Bagherinejad, M. R.; Sadeghi, H. M. M.; Abedi, D.; Chou, C. P.; Moazen, F.; Rabbani, M. (Research in Pharmaceutical Sciences, 2016)
Recombinant protein production in E. coli has several advantages over other expression systems. Misfolding, inclusion body formation, and lack of eukaryotic post translational modification are the most disadvantages of this system. Exporting of correctly folded proteins to the outside of reductive cytoplasmic environment through twin-arginine system could help to pass these limiting steps. Two signal sequences, TorA and SufI are used at N-terminal of human growth hormone (hGH) bearing DsbA gene sequence at C-terminal to enhance folding. The synthetic cassettes including the signal sequence, hGH and DsbA were transformed into E. coli BL21 (DE3) to study the effect of signal sequence and DsbA chaperone on translocation and folding of the protein. The results confirmed using signal sequence at N-terminal of targeted protein and coexpression with DsbA could transport proteins to the periplasmic space and culture media compared to control groups. Although there is no protein band of somatropin in SDS-Page of culture media samples when using SufI as signaling sequence, the study demonstrated TorA signal sequence could transport the target protein to the culture media. However, there was a considerable amount of hGH in periplasmic space when using SufI compared to control.